A Taxonomy of Manufacturing Strategies - Miller, Jeffrey G.; Roth, Aleda V. (Management Science, 1994)
This paper describes the development and analysis of a numerical taxonomy of manufacturing strategies. The taxonomy was developed with standard methods of cluster analysis, and is based on the relative importance attached to eleven competitive capabilities defining the manufacturing task of 164 large American manufacturing business units. Three distinct clusters of manufacturing strategy groups were observed. Though there is an industry effect, all three manufacturing strategy types are observed in various industries. The two main dimensions along which the manufacturing strategy groups differ are the ability of the firms in them to differentiate themselves from competition with their products and services, and the scope of their product lines and markets. A general method for mapping manufacturing strategies on these dimensions is described. For each manufacturing group, the relationships between the competitive capabilities (which describe the manufacturing task), the business context (the business unit strategy), manufacturing activities (manufacturing strategy choices), and manufacturing performance measures are explored and compared.